Effects of pH and location within a loin on pork quality - Andrews, B.S.; Unruh, John A.; Hunt, Melvin C.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty-one boneless pork loins were used to determine the influence of pH on quality characteristics. With increasing loin pH, instrumental values for L* (lightness) and b* (yellowness) of loins and chops decreased, and cooking losses of chops before 0 d and after 1 d of retail display also decreased. The pH had no effects on package losses or Warner-Bratzler shear force values of chops. Center loin chops (0 d and 1 d) had higher ratios of reflectance than blade and sirloin chops. Sirloin chops had higher ratio of reflectance than blade chops. Center loin chops had lower package losses than blade and sirloin chops. Blade chops had lower (more tender) WBS values than center loin and sirloin chops. Measuring loin pH can predict instrumental color (L*and b*) values as well as cooking losses.
Keywords: Swine; Pork chops; pH; Quality